Perbandingan Nilai Budaya Cerita Rakyat Daerah Aliran Sungai Kalimantan Tengah : (Kajian Hermeneutika Dan Intertekstual) - Petrus Poerwadi; Stefani Ratu Lestariningtyas; Yulina Mingvianita; Indra Perdana (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Central Kalimantan is a province in Indonesia located on Kalimantan Island. Most of the province's territory is covered by tropical rainforest. The lowlands are crossed by a swamp belt formed by the Lamandau, Arut, Seruyan, Katingan, Kahayan, Kapuas, and Barito rivers. Because Kalimantan has many river basins, its people also adhere to a way of life that is strongly influenced by nature. The values ​​contained in it are also the values ​​that exist in society. Central Kalimantan also has a lot of folklore because Central Kalimantan is divided into several Dayak tribes, and the unique topology of the region makes each folktale different. This research aims to represent society as presented through folk tales entitled Six Folk Tales of the Central Kalimantan watershed, describing the similarities and differences in values ​​in six folk tales, namely AMDM, TPTP, NBKA, KRPM, BTBI, and DBKBP originating from Barito, Kayahan, and Katingan. This research uses a qualitative descriptive research methodology. This research aims to describe the Comparison of Cultural Values ​​of Folklore in the Central Kalimantan River Basin (Hermeneutics and Intertextual Studies) as a representation of the values ​​of Dayak folklore in the Central Kalimantan River Basin. The Dayak people who live in the Central Kalimantan river basin certainly have unique values ​​compared to other areas of Central Kalimantan. Through a comparison of the six folktales, it can be seen that the cultural values ​​of the Dayak people include, among other things, cultural values ​​related to (1) cultural values ​​between humans, and (2) cultural values ​​with nature. , (3) cultural values ​​with society, and (4) human relationship with God.